Association between Gastric Cancer Risk and Serum Helicobacter pylori Antibody Titers. (11th June 2017) - Shuto, Mitsutaka; Fujioka, Toshio; Matsunari, Osamu; Okamoto, Kazuhisa; Mizukami, Kazuhiro; Okimoto, Tadayoshi; Kodama, Masaaki; Takigami, Shigeru; Seguchi, Chuichi; Nonaka, Yoshihito; Sato, Ryugo; Yamaoka, Yoshio; et al.
Abstract : Background/Aims . It is difficult to confirm the accurate cutoff value to diagnose Helicobacter pylori (Hp) infection using commercial serology kits. It is reported that there were many cases with present/past infection that even the serum Hp -IgG antibody ( Hp Ab) titers were below the cutoff value (e.g., 10 U/mL for E-Plate®), suggesting that we might overlook many gastric cancer (GC). We investigated an association between gastric cancer risk and serum Helicobacter pylori antibody titers. Methods . We conducted a primary screening between 2014 and 2015. We performed gastroendoscopy if Hp Ab titers were ≥3.0 U/mL (i.e., more than measurable limit, E-Plate). These patients were divided into two groups: Hp Ab = 3.0–9.9 U/mL ("negative-high" group) and Hp Ab ≥ 10 U/mL; cutoff value ("over-10 U/mL" group). Hp infection status was investigated, and the number of GC patients was counted. Results . Among the 3321 subjects in the primary screening, 56.9% (1891/3321) showed Hp Ab titers ≥3.0 U/mL; 1314 patients underwent gastroendoscopy. Ten were GC. 421 patients were "negative-high" group; two were GC. After evaluating 381 patients for Hp infection, 22.6%/60.6% was with present/past infection among the "negative-high" group. Conclusion . We also found a correlation between Hp Ab titers and Hp infection status. "Negative-high" group has a risk of GC.